Value-Based Peer Helpers in Indonesia’s Islamic Boarding Schools: Addressing Student Needs - Khusumadewi, Ari; Naqiyah, Najlatun; Setiawati, Denok; Pramesti, Mayang; Ariyanti, Vivin; Dewanti, Septinda Rima (Universitas Negeri Padang, 2024)
Islamic boarding schools (Pesantren) are crucial educational institutions in Indonesia, characterized by their unique learning systems, values, and diverse student demographics. However, they face challenges, such as a lack of sufficient caregivers and teachers, limiting their ability to address students' varied needs, which range across age, gender, culture, and personal concerns. This study aims to develop a peer helper model that integrates Islamic boarding school values to overcome these limitations and provide better support for students, particularly for adolescents. Using a literature review and content analysis of various reference sources, this study found that peer helpers, designed with pesantren values, offer an potential solution by addressing the students' challenges through peer relationships, which are more significant during adolescence. The peer helper model includes essential components such as selecting suitable peer helper characteristics, equipping them with necessary skills, and implementing effective support strategies. This culturally relevant model not only compensates for the limited availability and competence of caregivers and teachers but also provides a framework adaptable to other educational settings with similar issues. The integration of religious and cultural values into student support systems demonstrates the importance of culturally responsive approaches in enhancing student well-being in educational contexts.